Daughter Zions Contemporary Sibling Dalit Assertions vis–vis a Postcolonial Reading of the Book of Lamentations - Dominic S. Irudayaraj (P3TK, Sanata Dharma University, 2019)
Taking a cue from a perceptive and a widely-received work of Carleen Mandalfo (Daughter Zion Talks Back to the Prophets: A Dialogic Theology of the Book of Lamentations), the present paper aims to glean some of the salient multi-disciplinary insights of the author. The same insights are grouped around some of the salient postcolonial features that R. S. Sugirtharajah outlines, which together constitute postcolonial construal with attendant illustrations. Then, the paper shifts the spotlight on commensurate features in contemporary Dalit assertions from the Indian subcontinent in order to propose that the latter can be viewed as a meaningful, contemporary sibling of Daughter Zion. Despite the chronological and cultural distances between the Dalits and Daughter Zion of Lamentations, it is proposed here that the assertions of these two likewise siblings may profitably be appropriated by todays readers of courage and commitment in order to come to terms with the angsts and outbursts of people, particularly of those who reel under immense pain and fissure.